Effects of 12-weeks of Brisk Walking on Health-related Physical Fitness, Balance, and Life Satisfaction in Overweight Older Chinese Women: A Cluster Randomized Control Trial - Xiaorong Bai; Yuhui Wang; Feifei Chen; Zongqiang Jin; Wensheng Xiao; Soh Kim Geok (PLoS ONE, 2026)
Obesity among the elderly is primarily the result of a lack of exercise. Many people around the world are concerned about how physical activity can improve the life satisfaction and physical health of overweight seniors. As a result, this study aims to investigate how brisk walking impacts the physical fitness, balance, and overall quality of life of overweight senior women in China. This study design based on cluster randomized control trial. 54 older women between the ages of 60 and 69 were randomly assigned to the brisk walking group (n = 27) or the control group (n = 27). The brisk walking group received three times, (35-60) minutes sessions per week for 12 weeks, while the control group kept their daily routine. Data collection at zero week and twelfth week. Results have presented that brisk walking improved (p < 0.05) cardiorespiratory fitness, flexibility, muscular strength, muscular endurance, balance, and life satisfaction after 12-weeks intervention, except for body composition. Only the chair stand test of muscular endurance showed a significant difference between the brisk walking group and the control group after 12 weeks of training. Nevertheless, the effect size between the groups was increased after 12 weeks of training. In conclusion, brisk walking promotes health-related physical fitness, balance, and life satisfaction among overweight older women after 12 weeks intervention, except body composition.